From the mound to the square: the impact of the new yam festival on the Ogoja people. Issue 1 (2nd January 2023) - Odey, Patrick O
ABSTRACT: The agrarian disposition of man was facilitated by geography, the desire for food security, and metallurgy. As soon as sedentary life became possible, man started the domestication of wild plants. One of these was yam (Discorea spp.) which became not just a staple but widely acclaimed within the 'yam zone' as 'king crop'. This is because of the gender underpinning in its cultivation; where only men could cultivate it in large scale either through share-cropping or mono-cropping; and the pomp and pageantry associated with its harvest. The Ogoja people fall within this yam zone as evidence in the annual festival galore from August to September. Yam has therefore risen from its culinary, economic, and religious significance to tourism and political importance. It is in this light that this paper interrogates the economic, political, and socio-cultural impact of this annual event on the people from Obubra to Obanliku and Yala Local Government Areas of Cross River State given the current realities.